Conditioning open-label placebo: a pilot pharmacobehavioral approach for opioid dose reduction and pain control. (20th July 2020) - Morales-Quezada, Leon; Mesia-Toledo, Ines; Estudillo-Guerra, Anayali; O'Connor, Kevin C.; Schneider, Jeffrey C.; Sohn, Douglas J.; Crandell, David M.; Kaptchuk, Ted; Zafonte, Ross
Abstract : Given the complexity of pain management in rehabilitation settings, pharmaco-behavioral interventions can capitalize on the self-modulatory process to enhance the effects of a drug-based intervention. Abstract : Introduction: Opioid consumption for those in comprehensive inpatient rehabilitation units is high because of the complexity of their injuries. Notably, pain in rehabilitation leads to worsened clinical outcomes because of maladaptive behaviors and poor engagement during therapies. It is critical to developing evidence-based pharmacobehavioral interventions. Based on principles of classical conditioning, conditioning open-label placebo (COLP) is a promising approach for reducing opioid use in comprehensive inpatient rehabilitation, and this technique takes advantage of the possibility of association learning and opioid pharmacology to promote evoked placebo-driven analgesia. Objectives: In this brief report, we evaluate the feasibility of COLP as a pharmacobehavioral intervention to decrease total opioid consumption in patients with pain hospitalized at Spaulding Rehabilitation Hospital. Methods: Inpatients with spinal cord injury and polytrauma (n = 20) with moderate to severe pain were randomized to receive COLP (n = 10) or treatment-as-usual for 6 consecutive days. Opioid utilization was measured by morphine equivalents using the morphine equivalent dose conversion; pain severity was assessed using the numerical visual analog scale. Results: Conditioning open-label placebo significantly reduced total opioid consumption by the end of the intervention period ( P ≤ 0.001). Pain reduction was also significant for the COLP group ( P = 0.005), whereas the treatment-as-usual group demonstrated a trend towards pain reduction ( P = 0.05). Conclusions: This study presents the first data in the use of a pharmacobehavioral intervention that capitalize on the benefits of open-label placebo and classical drug conditioning for opioid dose reduction in a population with moderate to severe pain exposed to intensive inpatient rehabilitation.